Turbidite record of frequency and source of large volume (>100 km3) Canary Island landslides in the last 1.5 Ma: Implications for landslide triggers and geohazards. (8th July 2013) - Hunt, J. E.; Wynn, R. B.; Talling, P. J.; Masson, D. G.
Abstract : [1] During the last two decades, numerous studies have focused on resolving the landslide histories of the Canary Islands. Issues surrounding the preservation and dating of onshore and proximal submarine landslide deposits precludes accurate determination of event ages. However, submarine landslides often disaggregate and generate sediment gravity flows. Volcaniclastic turbidites sampled from Madeira Abyssal Plain piston cores represent a record of eight large‐volume failures from the Western Canary Islands in the last 1.5 Ma. During this time, there is a mean recurrence rate of 200 ka, while the islands of El Hierro and Tenerife have individual landslide recurrences of 500 ka and 330 ka, respectively. Deposits from the 15 ka El Golfo landslide from El Hierro and 165 ka Icod landslide from Tenerife are examined. This study also identifies potential deposits associated with the Orotava (535 ka), Güímar (850 ka), and Rogues de García landslides (1.2 Ma) from Tenerife, El Julan (540 ka), and El Tiñor (1.05 Ma) landslides from El Hierro, and the Cumbre Nueva landslide (485 ka) from La Palma. Seven of eight landslides occurred during major deglaciations or subsequent interglacial periods, which represent 55% of the time. However, all of the studied landslides occur during or at the end of periods of protracted island volcanism, which generally represent 60% of the island histories. Although climate may precondition failures, it is suggested that volcanism presents a more viable preconditioning and trigger mechanism for Canary Island landslides. Key Points: Madeira Abyssal Plain volcaniclastic deposits represent Canary Island landslides Turbidite composition and age correlate deposits to known landslides Landslides correlate to periods of volcanism and warmer climate conditions